Screen for alterations of iron related parameters in N-ethyl-N-nitrosourea-treated mice identified mutant lines with increased plasma ferritin levels - Rathkolb, Birgit; Klempt, Martina; Sabrautzki, Sibylle; Michel, Dian; Klaften, Matthias; Laufs, Jürgen; Sedlmeier, Reinhard; Hans, Wolfgang; Fuchs, Helmut; Muckenthaler, Martina; Horsch, Marion; Campagna, Dean R.; et al. (BioMetals, 2015)
Iron is essential for numerous cellular processes. For diagnostic purposes iron-related parameters in patients are assessed by clinical chemical blood analysis including the analysis of ferritin, transferrin and iron levels. Here, we retrospectively evaluated the use of these parameters in the phenotype-driven Munich N-ethyl-N-nitrosourea mouse mutagenesis project for the generation of novel animal models for human diseases. The clinical chemical blood analysis was carried out on more than 10,700 G1 and G3 offspring of chemically mutagenized inbred C3H mice to detect dominant and recessive mutations leading to deviations in the plasma levels of iron-related plasma parameters. We identified animals consistently exhibiting altered plasma ferritin or transferrin values. Transmission of the phenotypic deviations to the subsequent generations led to the successful establishment of three mutant lines with increased plasma ferritin levels. For two of these lines the causative mutations were identified in the Fth1gene and the Ireb2 gene, respectively. Thus, novel mouse models for the functional analysis of iron homeostasis were established by a phenotype-driven screen for mutant mice.
Gesehen am 10.06.2020